Brokerage in Property Business According to DSN-MUI Fatwa No. 9 - Aqly Mubarak; Afrizal Fadillah; Vita Sarasi (PT. Student Rihlah Indonesia, 2026)
This research analyzes the legal framework that governs the operation of intermediaries in the property sector through the lens of sharia economic law, emphasizing the regulatory function of DSN-MUI Fatwa No. 93/DSN-MUI/IV/2014 on intermediaries (wasathah). In the modern property market, brokerage services are essential to speed up transactions and improve market efficiency; however, their acceptance under Islamic law depends on a well-defined contractual framework and adherence to Sharia norms. This study uses a normative juridical method through a qualitative doctrinal examination of Islamic legal sources, DSN-MUI fatwas, and related legislative restrictions. The results show that property brokers are legally acceptable under Islamic law when executed through genuine Sharia contracts, specifically wakalah bi al-ujrah, ju'alah, or samsarah. These contractual agreements require transparency, mutual agreement, explicitly defined payments (ujrah), and exclusions of unfairness, fraud, or exploitation. The analysis shows that DSN-MUI Fatwa No. 93/2014 establishes a normative basis for brokerage practice by highlighting the mutual benefits (maslahah) for property owners, buyers, and intermediaries. This essay improves Islamic economic law by explaining the validity of property brokerage law and emphasizing its significance in promoting equality, legal certainty, and efficiency in contemporary property transactions.